2018
DOI: 10.1182/blood-2018-99-114145
|View full text |Cite
|
Sign up to set email alerts
|

Single-Cell RNA Sequencing Reveals Compromised Immune Microenvironment in Precursor Stages of Multiple Myeloma

Abstract: Introduction: In multiple myeloma (MM), despite well-characterized precursor states such as monoclonal gammopathy of undetermined significance (MGUS) and smoldering multiple myeloma (SMM), there is a lack of sufficient biomarkers to predict mechanisms of disease progression. Most genomic analyses have sought biomarkers by study of the malignant plasma cells, however, cancers form a complex ecosystem with the immune and stromal microenvironment. Thus, to characterize the cellular composition and transcriptional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…2). Cytotoxic CD8+ T-cell makers were collected from Zavidij et al 23 . Copy number analysis for the scRNAseq was done using CONICSmat(v0.1) 24 and plasma cells were compared with B cells as reference set.…”
Section: Methodsmentioning
confidence: 99%
“…2). Cytotoxic CD8+ T-cell makers were collected from Zavidij et al 23 . Copy number analysis for the scRNAseq was done using CONICSmat(v0.1) 24 and plasma cells were compared with B cells as reference set.…”
Section: Methodsmentioning
confidence: 99%
“…IL‐32 expression is also observed in malignant cells such as melanoma cells, colon cancer cells, and pancreatic and thyroid cancer tissues and cell lines 26–31 . Single cell seq studies have demonstrated that Tregs are important sources of IL‐32 in various diseases 13,32,33 . Even though IL‐32 can be expressed in basal conditions, more typically IL‐32 expression is induced or enhanced in response to pro‐inflammatory cytokines, infections, and other types of cellular stress such as hypoxia, as briefly outlined in the following section.…”
Section: Il‐32 Is Expressed In Several Cell Typesmentioning
confidence: 99%
“…Single cell seq studies have revealed that Tregs are important sources of IL‐32 in various diseases 13,33,32 …”
Section: Il‐32 Is Expressed In Several Cell Typesmentioning
confidence: 99%
“…MM is an excellent cancer immunoediting example in which a premalignant equilibrium phase—MGUS—anticipates the escape phase of active disease [ 13 , 14 ]. The precursor stages, as MGUS and SMM, already harbor malignant clones characterized by genomic changes (e.g., IgH translocations or hyperdiploidy) [ 15 , 16 ].…”
Section: Myeloma Immune Microenvironment: From Surveillance To Immmentioning
confidence: 99%